2015
DOI: 10.1002/ccd.26060
|View full text |Cite
|
Sign up to set email alerts
|

Primary percutaneous coronary intervention by drug‐eluting balloon angioplasty: The nonrandomized fourth arm of the DEB‐AMI (drug‐eluting balloon in ST‐segment elevation myocardial infarction) trial

Abstract: PPCI by DEB-only in selected patients yielded an angiographic outcome comparable to BMS alone and DEB followed by BMS. PES proved angiographic superiority to DEB-only. DEB-only is therefore a potential treatment alternative during PPCI in patients with contra-indications to drug-eluting stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…The efficacy of a DCB for the treatment of in‐stent restenosis is well‐established . A trial, however, showed that the angiographic outcome of a DCB‐only strategy was inferior to that of a DES implantation for patients with an acute myocardial infarction. The authors explained that a lack of structural support to the vessel was a crucial drawback of the DCB‐only strategy, and it may have outweighed its benefits such as an antiproliferative action and positive remodeling .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of a DCB for the treatment of in‐stent restenosis is well‐established . A trial, however, showed that the angiographic outcome of a DCB‐only strategy was inferior to that of a DES implantation for patients with an acute myocardial infarction. The authors explained that a lack of structural support to the vessel was a crucial drawback of the DCB‐only strategy, and it may have outweighed its benefits such as an antiproliferative action and positive remodeling .…”
Section: Discussionmentioning
confidence: 99%
“…A trial, however, showed that the angiographic outcome of a DCB‐only strategy was inferior to that of a DES implantation for patients with an acute myocardial infarction. The authors explained that a lack of structural support to the vessel was a crucial drawback of the DCB‐only strategy, and it may have outweighed its benefits such as an antiproliferative action and positive remodeling . Thus, so far, the DCB‐alone for the treatment of ACS is seen as a potential alternative strategy only for patients with contraindications to a DES .…”
Section: Discussionmentioning
confidence: 99%
“…Nijhoff et al in a subgroup analysis from the DEBAMI trial showed that there was no difference in major adverse cardiac events in 40 patients treated with DCBonly PPCI in comparison with BMS only, BMS + DCB, and paclitaxel-eluting stent implantation at 6 months follow-up [20].…”
Section: Evidence For Dcb Angioplasty In Ppcimentioning
confidence: 99%
“…Prompted by the promising DEB-only results from PEPCAD I and V, the investigators behind DEB-AMI established a fourth nonrandomized DEB-only arm [72]. The same inclusion criteria were applied, except that successful predilatation was mandatory before DEB treatment, presumably partly accounting for the low 10% bailout rate.…”
Section: Drug-eluting Balloonsmentioning
confidence: 99%